2009
DOI: 10.1080/10402000802105448
|View full text |Cite
|
Sign up to set email alerts
|

First Traction Results of High Spinning Large-Size Circular EHD Contacts from a New Test Rig: Tribogyr

Abstract: This article presents a new test rig named Tribogyr and the first results obtained so far. This device allows EHL friction tests in rolling-sliding under high spinning conditions applied to large-size circular contacts. Spinning is imposed thanks to a unique design that includes a tilting facility of one of the two spindles. After a brief description of the test rig structure and of the specimen geometry, the sensor's implementation and the device capabilities are reported. The parameter used to quantify the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…A closer look inside the contact (possible with the help of numerical investigation only) allowed to explain this effect [14]: with the addition of spin, a part of the contact area sees its longitudinal stresses becoming negative; the integration of these stresses leads to lower longitudinal friction than in a no-spin case. Comparison of this study with numerical and experimental friction data found in the literature [14,26] is presented in Fig. 9.…”
Section: Frictionmentioning
confidence: 92%
See 1 more Smart Citation
“…A closer look inside the contact (possible with the help of numerical investigation only) allowed to explain this effect [14]: with the addition of spin, a part of the contact area sees its longitudinal stresses becoming negative; the integration of these stresses leads to lower longitudinal friction than in a no-spin case. Comparison of this study with numerical and experimental friction data found in the literature [14,26] is presented in Fig. 9.…”
Section: Frictionmentioning
confidence: 92%
“…The friction coefficient (Cf x ) is represented as a function of the longitudinal slide-to-rolling ratio (equation (2)). The same kinematic conditions as Dormois et al [14] is simulated here: both experimental conditions and relevant numerical parameters can be found in references [14] and [26]: l ¼ 2 , U m,x,0 ¼ 2 m/s, U m,y,0 ¼ 0 m/s, p H ¼ 845 MPa, a ¼ 0.92 mm, and 2 varies between 680 and 840 rad/s to achieve the corresponding longitudinal slide-to-rolling ratio (SRR x,0 ). Although the same lubricant was investigated, Dormois et al used an isothermal Roelands Dowson-Higginson viscosity density model as well as a Ree-Eyring behaviour for the friction calculation.…”
Section: Frictionmentioning
confidence: 98%
“…In the present study, " h is selected as 10 nm. 19,20 Equation 7can be considered as a special form of equation (2). At the boundary between the hydrodynamic lubrication and asperity contact regions, the pressure is consistent.…”
Section: Pressure Control Equation and Load Balance Equationmentioning
confidence: 99%
“…By introducing an effective viscosity * into equation (2), the non-Newtonian properties of lubricant can be considered. The sinh-law model 21,22 is used, and the effective viscosity * can be expressed as…”
Section: Rheological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation